Maternal and child health nursing : care of the childbearing and childbearing family - Pillitteri, Adele (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2010)
Now in a fully revised and updated sixth edtion, this extraordinary introduction to maternal-child nursing helps you understand wellness and illness as family-centered events.
Unit 1: Maternal and child health nursing practice -- Unit 2: The nursing role in preparing families for childbearing and childrearing -- Unit 3: The nursing role in caring for families during normal pregnancy, birth, the postpartum, and newborn period -- Unit 4: The nursing role in caring for a family during a complicaton of pregnancy, birth, or the postpartal period -- Unit 5: The nursing role in health promotion for a childrearing family
Includes index.
Keywords: MATERNITY NURSING